Let's continue solving the equation step by step.
1. We began with:
[tex]\[
7(x - 3) = 28
\][/tex]
2. Applying the distributive property, we expanded the equation to:
[tex]\[
7x - 21 = 28
\][/tex]
3. Next, we applied the addition property of equality by adding 21 to both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[
7x - 21 + 21 = 28 + 21
\][/tex]
Simplifying this, we get:
[tex]\[
7x = 49
\][/tex]
4. Finally, using the division property of equality, we divide both sides by 7 to solve for [tex]\( x \)[/tex]:
[tex]\[
x = \frac{49}{7}
\][/tex]
Hence, the value of [tex]\( x \)[/tex] is:
[tex]\[
x = 7
\][/tex]
Among the options given:
- 7
- 9
- 42
- 56
The correct value of [tex]\( x \)[/tex] is [tex]\( \boxed{7} \)[/tex].